Depth‐dependent mechanisms regulate accumulation of plant‐ and microbial‐derived residues under long‐term nitrogen addition in a semiarid grassland - Yuan, Xiaobo; Yao, Shize; Zhou, Guiyao; Frew, Adam; Dietrich, Peter; Li, Yuan; Wang, Ying; Ma, Tian; Chen, Ning; Zhang, Yaodan; Xu, Jingrun; Wu, Shujuan; et al. (Wiley-Blackwell, 2026)
Plant- and microbial-derived residues constitute the primary sources of soil organic carbon (SOC) in grassland ecosystems. However, their differential responses to chronic nitrogen (N) enrichment and the depth-dependent mechanisms governing their accumulation remain poorly characterized, particularly for water-limited grassland systems. Based on a 13-year field experiment in a semiarid grassland, we quantified the effects of long-term N addition on the accumulation of plant- (lignin phenols) and microbial-derived (amino sugars) residues. We found that N addition significantly increased lignin phenol content and its contribution to SOC in the topsoil, whereas lignin phenols exhibited a hump-shaped response peaking under moderate N levels in the subsoil. Amino sugar concentrations and their relative contribution to SOC increased in both soil layers under N addition but declined at the highest N input. The dominant factors regulating residue accumulation varied with soil depth: in the topsoil, microbial K−/r-traits and community composition primarily explained lignin phenol and amino sugar dynamics, while in the subsoil, mineral-associated protection and microbial composition were the key drivers. These findings underscore the depth-dependent nature of SOC formation pathways and highlight the importance of incorporating both plant- and microbial-derived residues into Earth System Models to improve projections of carbon-climate feedback under changing nitrogen regimes.
Keywords: amino sugars; lignin phenols; microbial K-/r-traits; microbial residues; mineral protection; nitrogen depositio